Gambaran SpO2 Saat Masuk dan Keluar Rumah Sakit pada Pasien COVID-19 - Kevinsi E. Kaligis; Hedison Polii; Vanda Doda (eBiomedik, 2022)
Abstract: The COVID-19 pandemic that has occurred since 2019 has claimed millions of victims worldwide. An examination that can assess how severe the condition of a COVID-19 patient is is an oxygen saturation test. Pulse oximetry is a tool used to measure oxygen saturation values. This study aims to determine the description of oxygen saturation when entering and leaving the hospital for COVID-19 patients at the Robert Wolter Mongisidi Hospital, Manado. The method in this study was retrospective descriptive, collecting secondary data in the form of medical records of patients who were confirmed positive for COVID-19. Based on secondary data obtained from January to September 2021, the number of samples in this study was 251. At the time of admission to the hospital 60.1 men and 39.9% women. In the elderly and children there is a significant improvement in saturation where when out of the hospital there is no oxygen saturation below normal. On admission to the hospital the average oxygen saturation was 96.55% and when discharged from the hospital the average oxygen saturation value was 98.11%. %. On discharge from the hospital there were 4 (2%) cases that had oxygen saturation <94%, the four patients were probably referred or forced to go home. In conclusion, there was an improvement in oxygen saturation levels when leaving the hospital for COVID-19 patients at the Robert Wolter Mongisidi Hospital in Manado for the period January-September 2021Keywords: Oxygen Saturatio; COVID-19 Abstrak: Pandemi COVID-19 yang terjadi sejak tahun 2019 sudah  memakan jutaan korban di dunia. Pemeriksaan yang dapat menilai seberapa berat kondisi pasien COVID-19 adalah pemeriksaan saturasi oksigen. Pulse oximetry merupakan alat yang digunakan untuk mengukur nilai saturasi oksigen. Penelitian ini bertujuan untuk mengetahui gambaran saturasi oksigen saat masuk dan keluar rumah sakit pada pasien COVID-19 di RS Robert Wolter Mongisidi Manado. Metode dalam penelitian ini adalah deskriptif retrospektif, mengumpulkan data sekunder berupa rekam medik pasien terkonfirmasi positif COVID-19. Berdasarkan data sekunder yang didapat sejak bulan Januari sampai September 2021,  jumlah sampel dalam penelitian ini adalah 251. Saat masuk rumah sakit pada laki-laki 60,1 dan pada perempuan 39,9%. Pada lansia dan anak-anak mengalami perbaikan saturasi yang signifikan dimana saat keluar rumah sakit tidak terdapat saturasi oksigen dibawah normal. Saat masuk rumah sakit rata-rata saturasi oksigen 96,55% dan saat keluar rumah sakit nilai rata-rata saturasi oksigen 98,11%. Saat keluar rumah sakit terdapat 4 (2%)  kasus yang memiliki saturasi oksigen <94%, keempat pasien tersebut kemungkinan dirujuk atau pulang paksa. Sebagai simpulan, terdapat perbaikan kadar saturasi oksigen saat keluar rumah sakit pada pasien COVID-19 di Rumah Sakit Robert Wolter Mongisidi Manado periode bulan Januari-September 2021.  Kata kunci: Saturasi Oksigen; COVID-19